SsNEP2 Contributes to the Virulence of Sclerotinia sclerotiorum - Chenghuizi Yang; Wei Li; Xingchuan Huang; Xianyu Tang; Lei Qin; Yanan Liu; Yunong Xia; Zhihong Peng; Shitou Xia (Pathogens, 2022)
Sclerotinia sclerotiorum is a notorious soilborne fungal pathogen that causes serious economic losses globally. The necrosis and ethylene-inducible peptide 1 (NEP1)-like proteins (NLPs) were previously shown to play an important role in pathogenicity in fungal and oomycete pathogens. Here, we generated S. sclerotiorum necrosis and ethylene-inducible peptide 2 (SsNEP2) deletion mutant through homologous recombination and found that SsNEP2 contributes to the virulence of S. sclerotiorum without affecting the development of mycelia, the formation of appressoria, or the secretion of oxalic acid. Although knocking out SsNEP2 did not affect fungal sensitivity to oxidative stress, it did lead to decreased accumulation of reactive oxygen species (ROS) in S. sclerotiorum. Furthermore, Ssnlp24SsNEP2 peptide derived from SsNEP2 triggered host mitogen-activated protein kinase (MAPK) activation, increased defense marker gene expression, and enhanced resistance to Hyaloperonospora arabidopsidis Noco2. Taken together, our data suggest that SsNEP2 is involved in fungal virulence by affecting ROS levels in S. sclerotiorum. It can serve as a pathogen-associated molecular pattern (PAMP) and trigger host pattern triggered immunity to promote the necrotrophic lifestyle of S. sclerotiorum.